Unscented transformation method for robustness verification of helicopter flight control system - LIU Changqi; LI Aijun; DUAN Guangzhan; LI Zuo (Hangkong gongcheng jinzhan, 2025)
In response to the large computational load and extended processing time associated with the Monte Carlo method in the robustness verification of helicopter flight control systems, this paper proposes an unscented transformation method for such verification. This method employs particle swarm optimization for determining the uncertain parameters. Using the helicopter′s yaw channel as a case study, the unscented transformation method′s performance in robustness verification is compared with that of the Monte Carlo method. The results show that the unscented transformation method significantly enhances computational efficiency while maintaining comparable accuracy to the Monte Carlo method in the robustness verification of helicopter flight control systems. By adjusting parameter values to modulate the distance between sampling points and the sample center, this method is also suitable for the robustness verification of high-dimensional helicopter flight control systems.